PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING DENGAN TEHNIK MAKE A MATCH UNTUK MENINGKATKAN PRESTASI BELAJAR IPS SISWA KELAS VII SMP NEGERI 1 GESI KABUPATEN SRAGEN TAHUN PELAJARAN 2014/2015 - Ariati, Wiji; Sariyatun, S.; Agung S., Leo (Sebelas Maret University (UNS), 2015)
This study aims to describe: (1) To determine the application of learning models Cooperative Learning to Make A Match technique in teaching social studies at VIIE grade students of SMP Negeri 1 Gesi Sragen the academic year 2014/2015. (2) To determine the Application of Cooperative Learning learning model with Make A Match technique can improve learning achievement IPS VIIE grade students of SMP Negeri 1 Gesi Sragen the academic year 2014/2015. This study uses a Class Action Research (Classroom Action Research). The subjects of this study were students of class VII E SMP Negeri 1 Gesi Sragen. This data collection is done by using interviews, tests, observation, and questionnaires. Mechanical engineering data validity checking with triangulation method. Technical analysis is done by penggumpulan of data, data reduction, data presentation, and conclusion. The research process conducted three cycles, in each cycle includes four stages: planning action, action, observation and reflection. The results showed that: (1) Implementation of the learning model of Cooperative Learning to Make A Match technique in teaching social studies in the seventh grade students of SMP Negeri 1 Gesi can be implemented properly. Students can be encouraged to learn while playing, in a manner to match each card being owned. IPS Learning becomes more interesting, students more easily understand the content of the material presented by the teacher, because the students have been preparing for study before following study. (2) Research has been carried out proved that the learning outcomes of students in participating in the learning process is increasing. In the pre-cycle the number of children while that scored in the top 75 a total of 11 students (34.38%) . While the first cycle while children who scored in the top 75 to as many as 14 students or 43.75% of the the total number of students. In the second cycle while the students who scored in the top KKM (75) as many as 23 students or 71.8% on the number of students entirely. The third cycle students who scored in the top 75 by 28, or 87.9% with an average of 85.6 hump.